A Modified Method Based on the Discrete Sliding Norm Transform to Reduce the PAPR in OFDM Systems - Salmanzadeh, R.; Tazehkand, B. Mozaffari (ETRI journal, 2014)
Orthogonal frequency division multiplexing (OFDM) is a modulation technique that allows the transmission of high data rates over wideband radio channels subject to frequency selective fading by dividing the data into several narrowband and flat fading channels. OFDM has high spectral efficiency and channel robustness. However, a major drawback of OFDM is that the peak‐to‐average power ratio (PAPR) of the transmitted signals is high, which causes nonlinear distortion in the received data and reduces the efficiency of the high power amplifier in the transmitter. The most straightforward method to solve this problem is to use a nonlinear mapping algorithm to transform the signal into a new signal that has a smaller PAPR. One of the latest nonlinear methods proposed to reduce the PAPR is the L2‐by‐3 algorithm, which is based on the discrete sliding norm transform. In this paper, a new algorithm based on the L2‐by‐3 method is proposed. The proposed method is very simple and has a low complexity analysis. Simulation results show that the proposed method performs better, has better power spectral density, and is less sensitive to the modulation type and number of subcarriers than L2‐by‐3.